The Namibian Children's Heart Project: a South–South partnership to provide cardiac care. (20th February 2019) - Shidhika, Fenny F.; Hugo-Hamman, Christopher T.; Lawrenson, John B.; Du Toit, Henning J.; Vosloo, Susan M.; Brooks, Andre; Pribut, Harold S.; Perkins, Susan R.; Zühlke, Liesl J.
Abstract: Introduction: Congenital and acquired heart diseases are highly prevalent in developing countries despite limited specialised care. Namibia established a paediatric cardiac service in 2009 with significant human resource and infrastructural constraints. Therefore, patients are referred for cardiac interventions to South Africa. Objectives: To describe the diagnoses, clinical characteristics, interventions, post-operative morbidity and mortality, and follow-up of patients referred for care. Methods: Demographics, diagnoses, interventions, intra- and post-operative morbidity and mortality, as well as longitudinal follow-up data of all patients referred to South Africa, were recorded and analysed. Results: The total cohort constituted 193 patients of which 179 (93%) had CHD and 7% acquired heart disease. The majority of patients (78.8%) travelled more than 400 km to Windhoek before transfer. There were 28 percutaneous interventions. Palliative and definitive surgery was performed in 27 and 129 patients, respectively. Out of 156 patients, 80 (51.3%) had post-operative complications, of which 15 (9.6%) were a direct complication of surgery. Surgical mortality was 8/156 (5.1%, 95% confidence interval 2.2–9.8), with a 30-day mortality of 3.2%. Prolonged ICU stay was associated with a 5% increased risk of death with hazard ratio 1.05, 95% confidence interval 1.02–1.08, p=0.001. Follow-up was complete in 151 (78%) patients for more than 7 years. Conclusions: Despite the challenges associated with a cardiac programme for referring patients seeking intervention in a neighbouring country and the adverse characteristics of multiple lesions and complexity associated with late presentation, we report good surgical and interventional outcomes. Our goal remains to develop a comprehensive sustainable cardiac service in Namibia.